Opening huisvlijttentoonstelling ter gelegenheid van het 56-jarig bestaan van de ANDB. Zie ook BG B12/127-9
Opening huisvlijttentoonstelling ter gelegenheid van het 56-jarig bestaan van de ANDB. Zie ook BG B12/127-9.